Wetland Plants: Biology and Ecology - Cronk, Julie K (CRC Press, 2009)
A detailed account of the biology and ecology of vascular wetland plants and their applications in wetland plant science, Wetland Plants: Biology and Ecology presents a synthesis of wetland plant studies and reviews from biology, physiology, evolution, genetics, community and population ecology, environmental science, and engineering. It provides a thorough discussion of the range of wetland plants adaptations to conditions such as life in water or saturated soils, high salt or high sulfur, as well as low light and low carbon dioxide levels.